2014
DOI: 10.1111/ijcp.12461
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the endorse study results on thromboprophylaxis prescribing patterns in medical patients attending the Emergency Department

Abstract: The adequacy of thromboprophylaxis in high risk patients for VTE has improved compared with the ENDORSE study. However, the percentage of patients with discordant prescriptions remains high. Despite the existence of treatment omissions, this percentage has been overcome by patients overtreated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…This disappointing portrait of the contemporary use of inhospital medical thromboprophylaxis remains comparable to those previously reported. Twenty years ago, Cohen et al observed an adequate thromboprophylaxis rate as low as 39.5% in medical inpatients [6] and subsequently several authors described an adequacy of 50-60% at most [7][8][9][10].In Switzerland, Chmelik et al in 2002 found an inadequate thromboprophylaxis in 42% of high-risk patients and in almost 50% of low-risk patients [17]. Chopard et al in 2005 presented the results of a longitudinal survey in 1372 patients at eight Swiss hospitals (both teaching and nonteaching), with inadequate prophylaxis in 44.9% and 41.3% of high-and low-risk patients, respectively, with no difference in adequacy between teaching and nonteaching hospitals [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This disappointing portrait of the contemporary use of inhospital medical thromboprophylaxis remains comparable to those previously reported. Twenty years ago, Cohen et al observed an adequate thromboprophylaxis rate as low as 39.5% in medical inpatients [6] and subsequently several authors described an adequacy of 50-60% at most [7][8][9][10].In Switzerland, Chmelik et al in 2002 found an inadequate thromboprophylaxis in 42% of high-risk patients and in almost 50% of low-risk patients [17]. Chopard et al in 2005 presented the results of a longitudinal survey in 1372 patients at eight Swiss hospitals (both teaching and nonteaching), with inadequate prophylaxis in 44.9% and 41.3% of high-and low-risk patients, respectively, with no difference in adequacy between teaching and nonteaching hospitals [18].…”
Section: Discussionmentioning
confidence: 99%
“…In an international study of 70,000 patients in >300 hospitals in 2006-2007, the use Dr. Marco Marando Service de Pneumologie Hôpitaux Universitaires de Genève CH-1211 Genève marco.marando[at]aol.com of thromboprophylaxis was appropriate in only 58.5% of surgical and 39.5% of medical inpatients at risk of venous thromboembolism [6]. More recent estimates suggest an adequacy of thromboprophylaxis of 60-70% [7,8]. In Switzerland, its adequacy is also low, at 38-47% according to a multicentre prospective cohort (2010-2011) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, the ENDORSE study, considered the largest study to address this issue, evaluated both the risk of VTE and the adequacy of thromboprophylaxis in 68 183 patients from 358 hospitals in 32 countries 3 4. This study revealed a large number of patients at high risk of VTE not receiving thromboprophylaxis according to the American College of Chest Physicians (ACCP) 2004 guidelines;5 it also showed that the use of preventive measures in surgical patients (58.5%) was more frequent than in medical patients (39.5%).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, De Lorenzo‐Pinto et al. present the findings of a study which claims to examine the impact of the findings of the ENDORSE study on prescribing patterns for thromboprophylaxis in patients attending the emergency department in a tertiary care hospital in Spain. What this study assesses though, is a comparison of actual practice in the hospital against the recommendations made by the current ACCP guidelines.…”
mentioning
confidence: 99%
“…The study by De Lorenzo‐Pinto et al. highlights the fact that active measures to increase the prescription of thromboprophylaxis are likely to have the side effect of increasing unnecessary prescriptions as well. Thus, a careful balance must be sought.…”
mentioning
confidence: 99%